New data on the morphology of some Far-Eastern species of Rhabdochona (Nematoda: Rhabdochonidae), as revealed by SEM observations - Moravec, František; Ermolenko, Aleksei V; Besprozvannykh, Vladimir V; Scholz, Tomáš (Folia parasitologica, 2012)
Specimens of the nematode genus Rhabdochona Railliet, 1916 (Rhabdochonidae) were collected during helminthological examination of four species of cyprinid fishes in two rivers of the Amur River basin in the Russian Far East (Primorsky Region) in June 2011. Detailed light microscopical (LM) and scanning electron microscopical (SEM) examinations (the latter used for the first time for the reported nematode species) of the available material revealed the presence of three inadequately described nominal species of this genus: R. (Rhabdochona) denudata (Dujardin, 1845) from the spotted steed Hemibarbus maculatus Bleeker (Gobioninae), and R. (Rhabdochona) longispicula Belous in Roytman, 1963 and R. (Globochonoides) coronacauda Belous, 1965 from Culter alburnus Basilewsky (Cultrinae) in the Ilistaya River. Detailed morphological study of these worms, especially SEM examination, made it possible to reveal some previously unreported morphological features (e.g., the presence of sublabia or the character of ventral precloacal ridges) and to confirm other taxonomically important characters such as the shape of deirids, number of anterior prostomal teeth, number and situation of lateral preanal and postanal papillae or the detailed structure of the crown-like formation on the female tail tip in R. coronacauda. Unidentifiable Rhabdochona (Rhabdochona) gravid females were recorded from the humpback Chanodichthys dabryi (Bleeker) (Cultrinae) in the Ilistaya River and from the Amur minnow Rhynchocypris lagowskii (Dybowski) (Leuciscinae) in the Komissarovka River.
Keywords: Russia; hlístice; druhová specificita; Male; Fish Diseases; Nematoda; řeky; mužské pohlaví; Rivers; Species Specificity; ryby; Fishes; Animals; ženské pohlaví; Microscopy, Electron, Scanning; zvířata; nemoci ryb; Rusko; Female; mikroskopie elektronová rastrovací